MERDEKA BELAJAR: Pembelajaran Kewirausahaan untuk Meningkatkan Minat Berwirausaha - Nurhidayani Nurhidayani; Trisno Martono; Dewi Kusuma Wardani (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Todaywehaveenteredthe era ofindustrialrevolution 4.0 which requires more capabilities to be able to compete in the industrial world and the business world. Entrepreneurship education in higher education is a pedagogical program or educational process to form entrepreneurial attitudes and skills that involve self-development. It has the main goal to improve the competence of graduates to become independent and professional individuals. The improvement of the entrepreneurship program through Merdeka Belajar- Kampus Merdeka is aimed at improving soft skills and hard skills. This is done so that the graduates are better prepared with various competencies that suit the needs of the times. This program prepares graduates as future leaders of a superior and personal nation. The purpose of this research is to examine the application of entrepreneurial learning in universities. Preparation using descriptive qualitative with literature study method. The results showed that entrepreneurial learning can increase entrepreneurial interest, butfrom these advantages, there are still many obstacles for universities in the implementation of entrepreneurial learning, including the difficulty of implementing learning oriented to increase the entrepreneurial potential of students